Urbanization‐driven homogenization is more pronounced and happens at wider spatial scales in nocturnal and mobile flying insects. Issue 10 (11th July 2019) - Merckx, Thomas; Van Dyck, Hans
Abstract: Aim: We test whether urbanization drives biotic homogenization. We hypothesize that declines in abundance and species diversity of aerial insects are exacerbated by the urbanization‐driven loss of species with low habitat generalism, mobility and warm‐adaptedness. We predict this homogenization to be more pronounced for nocturnal taxa, and at wider scales for mobile taxa. Location: Belgium. Time period: Summers 2014–2015. Major taxa studied: Lepidoptera. Methods: We compare communities along urbanization gradients using a shared, replicated and nested sampling design, in which butterflies were counted within 81 grassland and macro‐moths light‐trapped in 12 woodland sites. We quantify taxonomic and functional community composition, the latter via community‐weighted means and variation of species‐specific traits related to specialization, mobility and thermophily. Using linear regression models, variables are analysed in relation to site‐specific urbanization values quantified at seven scales (50–3, 200 m radii). At best‐fitting scales, we test for taxonomic homogenization. Results: With increasing urbanization, abundance, species richness and Shannon diversity severely declined, with butterfly and macro‐moth declines due to local‐ versus landscape‐scale urbanization (200 vs. 800–3, 200 m radii, respectively). While taxonomic homogenization was absent for butterflies, urban macro‐moth communities displayed higher nestedness than non‐urban communities. Overall, communities showed mean shifts towards generalist, mobile and thermophilous species, displaying trait convergence too. These functional trait models consistently fit best with urbanization quantified at local scales (100–200 m radii) for butterfly communities, and at local to wider landscape scales (200–800 m radii) for macro‐moth communities. Main conclusions: Urban communities display functional homogenization that follows urbanization at scales linked to taxon‐specific mobility. Light pollution may explain why homogenization was more pronounced for the nocturnal taxon. We discuss that urbanization is likely to impact flying insect communities across the globe, but also that impacts on their ecosystem functions and services could be mitigated via multi‐scale implementation of urban green infrastructure.